Asuhan Keperawatan Jiwa Pada Pasien Gangguan Persepsi Sensori: Halusinasi Pendengaran Dengan Pemberian Intervensi Ocupation Therapy Menggambar Di Yayasan Rehabilitasi Mental Griya Bakti Medika Semanan 2024 - Latifah Maulina; Ayu Pratiwi; Mukhamad Saeful (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Mental disorders have experienced a significant increase, according to WHO 2023, mental disorders with hallucinations in Indonesia are 9.8% to 10.35% occurring in DKI Jakarta. Hallucinations are mental disorders that affect the function of perception or perception of the environment without real stimulus, resulting in interpreting something that is not real without external stimulus or stimulation (Stuart, 2021). One way to divert hallucinations is by implementing occupational intervention by drawing in addition to providing pharmacological therapy. Aim of Scientific Work: To determine the application of nursing care to patients with hallucinations by providing drawing occupational therapy intervention on changes in sensory perception. Method: this scientific work uses case study data collection methods by observation, interviews, documentation, and uses case study instruments in the format of Nursing Care and Occupational Drawing Intervention. Results: The results of the final scientific work of the nurses showed an analysis of nursing care after the intervention was carried out for 3 days within ± 45 minutes, it was found that nursing actions and innovations in the Drawing Occupation intervention had positive results, the client's symptoms of hallucinations decreased and the client's ability to divert with the Drawing Occupation increased, Clients are able to carry out interventions that are taught independently and with the correct procedures. The role of nurses in dealing with hallucinations in patients at home and in hospitals, one of which is implementing the Occupational Drawing Intervention. Conclusion: It was found that after carrying out occupational therapy drawing in patients with auditory hallucinations, there was a significant change in hallucinations